Computer aided testing of materials through interfacing device. (2021) - Asha, P.; Prabakar, D.; Anand, Sruthi; Karthik, M.; Sujin, J.S.; Ramesh Kumar, R.
Abstract: The computer aided material testing is playing an essential role in manufacturing industries to enhance the quality of the products. In recent years, the conventional machines are converted in to computer based control. The present paper was discussed about the material testing equipments have been updated with data acquisition and computer control system. The sensors and actuators were interfaced with computer control system. It was used to test the advanced material with high accuracy. The experimental purpose, aluminium and steel were used as testing materials. Tensile test and impact test were conducted. The experimental results were compared with or without interface system. The improved results were also discussed with pareto chart.